Tanggung Jawab Konstitusional Negara terhadap Perlindungan Data Pribadi Warga dalam Penyelenggaraan Pemerintahan Digital - Wiredarme (IPDN Kampus NTB, 2025)
This study aims to analyze the position of personal data as part of citizens’ constitutional rights in the implementation of digital government and to formulate the constitutional responsibility of the state in ensuring personal data protection. This research uses a qualitative method with a normative juridical approach. The study applies statutory, conceptual, and normative-contextual case approaches. The data sources consist of primary, secondary, and tertiary legal materials collected through library research. The analysis is conducted qualitatively and prescriptively through legal interpretation and legal reasoning. The findings show that citizens’ personal data cannot be understood merely as administrative information, but must be positioned as part of constitutional rights related to privacy, security, dignity, and personal protection. Law Number 27 of 2022 on Personal Data Protection provides a normative basis for linking personal data protection with the guarantee of the constitutional rights of data subjects. In the context of digital government, the state does not only act as a regulator, but also as a data controller, digital service provider, supervisory actor, and guarantor of citizens’ rights recovery. This study proposes five parameters of the state’s constitutional responsibility: legality of data processing, purpose limitation, system security, transparency and access for data subjects, and rights recovery. The findings imply that personal data governance in digital government must move beyond administrative compliance toward stronger constitutional accountability in protecting citizens’ rights.